Sistem Informasi Program Diet untuk Pasien Diabetes dan Hipertensi di Puskesmas Purwareja Klampok 1 Banjarnegara - Apri Listanti; Ahmad Aftah Syukron (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Diabetes Mellitus (DM) and hypertension are non-communicable diseases whose prevalence continues to increase in Indonesia. Purwareja Klampok 1 Health Center faces challenges in providing appropriate diet program services for DM and hypertension patients. This study aims to develop a web-based diet program information system that can help patients organize their daily menus and facilitate medical personnel in monitoring. The development method used is Rapid Application Development (RAD). The implementation results show that this system is able to provide personal diet information and facilitate monitoring of patient diet progress.